2017
DOI: 10.18632/oncotarget.23713
|View full text |Cite
|
Sign up to set email alerts
|

Natural and molecular history of prolactinoma: insights from aPrlr-/– mouse model

Abstract: Lactotroph adenoma, also called prolactinoma, is the most common pituitary tumor but little is known about its pathogenesis. Mouse models of prolactinoma can be useful to better understand molecular mechanisms involved in abnormal lactotroph cell proliferation and secretion. We have previously developed a prolactin receptor deficient (Prlr–/–) mouse, which develops prolactinoma. The present study aims to explore the natural history of prolactinoma formation in Prlr–/– mice, using hormonal, radiological, histol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…The data reported in this study (summarized in Fig. 8), together with former observations from us and several other groups [2, 39, 51, 54-57], support a new concept for the pathogenesis of prolactinomas. We suggest that PRLR signaling, involving the PRLR per se or effectors thereof, may favor a state of PRL resistance resulting in the downregulation of proapoptotic and antiproliferative effects that are mandatory for pituitary homeostasis, thereby promoting tumor development.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The data reported in this study (summarized in Fig. 8), together with former observations from us and several other groups [2, 39, 51, 54-57], support a new concept for the pathogenesis of prolactinomas. We suggest that PRLR signaling, involving the PRLR per se or effectors thereof, may favor a state of PRL resistance resulting in the downregulation of proapoptotic and antiproliferative effects that are mandatory for pituitary homeostasis, thereby promoting tumor development.…”
Section: Discussionsupporting
confidence: 87%
“…Of interest, it has been proposed that a loss-of-function PRLR mutation leads to hyperprolactinemia [53]. In addition, recent studies in PRLR-deficient female mice showed that cabergoline, a dopamine receptor 2 agonist, potently suppressed hyperprolactinemia but did not induce tumor shrinkage after 3 months of treatment [54], suggesting that PRLR activity is necessary for the control of lactotrope cell turnover. In fact, prolactinomas are currently being revisited as “pathologies of signaling pathways” [51].…”
Section: Discussionmentioning
confidence: 99%
“…PRL has been shown to promote the proliferation and differentiation of various types of cancer cells 16 , 25 . It does so by activating associated signaling pathways via JAK2 phosphorylation of signal transducers and activators of transcription (STAT), protein kinase C and phosphatidylinositol 3-kinase (PI3K) and mitogen-activated protein kinase (MAPK) in cells that express PRLR 16 , 39 - 41 .…”
Section: Resultsmentioning
confidence: 99%
“…PRL has been shown to promote the proliferation and differentiation of various types of cancer cells 16 , 25 . It does so by activating associated signaling pathways via JAK2 phosphorylation of signal transducers and activators of transcription (STAT), protein kinase C and phosphatidylinositol 3-kinase (PI3K) and mitogen-activated protein kinase (MAPK) in cells that express PRLR 16 , 39 - 41 . Although the majority of prolactinomas express both PRLR and ERα 13 , 16 , 29 , 35 , to the best of our knowledge, the effects of PRL on prolactinoma cell ERα signaling are yet to be elucidated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation